The amphibamiform Nanobamus macrorhinus from the early Permian of Texas. (March 2020) - Gee, Bryan M.; Reisz, Robert R.
Abstract: Nanobamus macrorhinus Schoch and Milner, 2014 is a small amphibamiform temnospondyl from the early Permian Arroyo Formation of Texas. It is most readily characterized by an elongate and partially subdivided naris. This condition is superficially reminiscent of that seen in the coeval trematopids, the group to which N. macrorhinus was originally referred to under an interpretation of the holotype as a larval form. This was discounted by later workers, but the amphibamiform affinities of the specimen were not formalized until recently. The specimen has never been described in the context of its amphibamiform affinities and remains poorly characterized, never having been sampled in a phylogenetic analysis. Here we present a complete, updated osteological description of N. macrorhinus, including an improved characterization of its unique mosaic of plesiomorphic and apomorphic features and clarification of the taxon's autapomorphies. Our analysis of the taxon's phylogenetic position within Amphibamiformes shows that N. macrorhinus was recovered as diverging after basal amphibamiforms, e.g., the micropholids, and before derived amphibamiforms, e.g., the amphibamids. This is supported by the unique mixture of retained plesiomorphies, e.g., nonforeshortened postparietals and an oval choana, and apomorphies, e.g., a narrow interorbital region and slender palatal rami of the pterygoid. These results reflect the complexity of terrestrial amphibamiform diversity and provide further insight into the evolutionary history of the lissamphibian stem in terrestrial environments.